Corporate Diversification, Firm Value and State Ownership in Chinese Publicly Listed Companies - Liu, Yang (2015)
Corporate diversification has long been a focused and deeply developed field, defined as the process of a company expand its business into different areas. There are mainly three different types of corporate diversification: product diversification (related or unrelated) and geographic market diversification (home market or international market). Our research is concentrated on the first form of diversification.